The Influence of Marketing Mix Variables on Decisions to Purchase a Subsidized Home - Khotimah, Nanda Khusnul; Firdaus, Muhammad; Yusuf, Hamzah Fanzuri (MBA : Journal of Management and Business Aplication, 2024)
PT Argopuro Pratama Sentosa is a real estate company in Banyuwangi Regency. Analysis of the Effect of Marketing Mix Variables on Subsidized House Purchase Decisions (Case Study in Taman Argopuro Indah Housing, Banyuwangi) is important to study along with the increasing proportion of households living in subsidized houses. Interviews, distribution of questionnaires, and documentation were used as data collection techniques. The sampling technique for this study used an accidental sampling technique, namely as many as 78 consumers at Taman Argopuro Indah Housing Complex. Data analysis methods in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, coefficient of determination test, f test, and t test. Based on the results of the F test, it shows that the marketing mix variables (price, location, product quality, and promotion) together have a positive and significant influence on the buying decision of subsidized housing. Based on the results of the t test, it can be seen that the variables of price, location, product quality, and promotion have a partially positive and significant effect on the purchase decision of subsidized housing.